Loneliness during the Pregnancy-Seeking Process: Exploring the Role of Medically Assisted Reproduction. (June 2023) - Köksal, Selin; Goisis, Alice
This study explores whether undergoing medically assisted reproduction (MAR) is associated with experiencing loneliness and whether this association varies by gender and having a live birth. Using two waves of the Generations and Gender Survey (n = 2, 725) from countries in Central and Eastern Europe, we estimate the changes in levels of emotional and social loneliness among pregnancy seekers in heterosexual relationships and test if they vary by the mode of conception while controlling for individual sociodemographic characteristics. Individuals who underwent MAR experienced increased levels of social loneliness compared to individuals who were trying to conceive spontaneously. This association is entirely driven by respondents who did not have a live birth between the two observation periods, while the results did not differ by gender. No differences emerged in emotional loneliness. Our findings suggest that increased social loneliness during the MAR process might be attributable to infertility-related stress and stigma.